Eficiência do protocolo superestimulatório P-36, associado à administração de eCG ou LH, em animais da raça Angus - Rosa, Fernanda de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The protocol called P-36 has been broad/y used to induce multiple ovulations, due to the fact that it allows fixed-time artificial insemination (FTAI), and facilitates embryo donors handling. Recent studies with P-36 protocol, have shownthat replacement of the last two doses of FSH by eCG improves embryo yield. However, after consecutive use, eCG may induce antibody and decrease bovine embryo production. The objective of the present study is to verify the efficiency of protocol P-36/eCG in Angus breed, and to test the replacement of eCG by LH in the last day of superestimulatory treatment. In experiment 1, 22 Angus cows were randomly allotted to 4 groups: LH60 (Control), LH60/eCG, LH60/LH and LH60/FSH+LH. Each donor was superovulated 3 times, in such a way that each animal received 3 of 4 treatments, totaling 17 cows in the first two groups and 16 in the others (incomplete block design). At a random stage of the estrous cycle (DO), the embryo donors received an intravaginal device (lVO) containing 1.0 9 of progesterone and estradiol benzoate (3.0 mg, i.m.). In the control group the animais were superestimulated with pFSH (i.m., total dose = 200 mg) twice a day in decreasing doses from 04 to 7, whereas in groups LH60/eCG and LH60/LH the last two doses of FSH were replaced by eCG (i.m, total dose = 400 lU) or LH (i.m., total dose = 2.0 mg), respectively. Finally, the cows trom group LH60/FSH+LH received two doses of 1.0 mg of LH simultaneously with the last two doses of FSH. Ali animais were treated with dc1oprostenol (150 mg, i.m.) on day 6, and the IVD was removed 36 h after PGF2a administration. Ovulation was induced with 12.5 mg of pLH (i.m.), on day 8, and the animais were FTAI 12 and 24 h after pLH. In experiment 2, 17 cows were randomly allocated in 3 groups: LH48, LH60 and LH48/FSH+LH. The difference between the first and the second experiment is that in groups LH48 and LH48/FSH+LH ... (Complete abstract click electronic access below)
Keywords: Bovino - Reprodução - Aspectos farmacológicos - Estudos experimentais; Inseminação artificial; Transferência de embriões; Farmacologia veterinaria; Bos taurus; Embryo transfer; Superovulation